2017
DOI: 10.1097/mpg.0000000000001297
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental and Familial Factors in a Cohort of Pediatric Patients With Inflammatory Bowel Disease

Abstract: Our study confirms that environmental factors are closely linked to IBD onset and may partly explain IBD rise in developed countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 39 publications
2
40
0
3
Order By: Relevance
“…The mechanisms of how MUFA might be beneficial in colitis are unknown, although adherence to the Mediterranean diet pattern has been shown to beneficially affect the gut microbiome and gut metabolites (metabolome) [35]. A recent case-control study ( n = 264 IBD subjects and 203 controls) found that low adherence to the Mediterranean diet pattern was a significant risk factor in the development of pediatric UC (OR: 2.3; 1.2–4.5) [36]. An intervention study examining the impact of the Mediterranean diet pattern in CD ( n = 8) demonstrated a trend for reduction in inflammatory biomarkers ( p = 0.39) and a tendency for “normalization” of the gut microbiota [37].…”
Section: Diet Interventions and Ibdmentioning
confidence: 99%
“…The mechanisms of how MUFA might be beneficial in colitis are unknown, although adherence to the Mediterranean diet pattern has been shown to beneficially affect the gut microbiome and gut metabolites (metabolome) [35]. A recent case-control study ( n = 264 IBD subjects and 203 controls) found that low adherence to the Mediterranean diet pattern was a significant risk factor in the development of pediatric UC (OR: 2.3; 1.2–4.5) [36]. An intervention study examining the impact of the Mediterranean diet pattern in CD ( n = 8) demonstrated a trend for reduction in inflammatory biomarkers ( p = 0.39) and a tendency for “normalization” of the gut microbiota [37].…”
Section: Diet Interventions and Ibdmentioning
confidence: 99%
“…A protective effect was observed in a diet enriched in vegetables, fruits, olive oil, fish, grains, and nuts in both genders among pediatric CD patients . Interestingly, Mediterranean diet could be one of anti‐inflammatory dietary patterns to meet the abovementioned demands and is recommended in our center, although limited studies supported this assumption in both UC and CD patients …”
Section: Diet In the Pathogenesis Of Ibdmentioning
confidence: 84%
“…68 Interestingly, Mediterranean diet could be one of anti-inflammatory dietary patterns to meet the abovementioned demands and is recommended in our center, although limited studies supported this assumption in both UC and CD patients. 70,71 3 | CLINICAL IMPLEMENTATION OF DIETARY INTERVENTIONS…”
Section: Dietary Patternmentioning
confidence: 99%
“…Accordingly, IBD has been reported in 21%-62% of children with lower GI bleeding in other studies (20)(21)(22)(23). Risk factors associated with IBD in children have been socioeconomic factors such as parents' educations and occupations, as well as nutritional factors including early (<6 month of age) gluten exposure (6). Life style is supposed to affect the risk of IBD development as IBD has been frequently associated with western culture (24).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of IBD in children is multifactorial. A history of IBD in siblings has been known as a traditional risk factor (6). There is a shortage of large population studies in pediatric IBD, and most available data on this come from adult onset IBD.…”
Section: Introductionmentioning
confidence: 99%